Egyptological Studies (1982)
Publications of the Hebrew University, Jerusalem; $30.00; A. F. Rainey: Palestinian place-names in the lists of Tuthmosis III; J. Vergote: Egyptian phrase in Akkadian in an Amarna vocabulary.